2014
DOI: 10.1139/apnm-2013-0336
|View full text |Cite
|
Sign up to set email alerts
|

Single and combined effects of beetroot juice and caffeine supplementation on cycling time trial performance

Abstract: Both caffeine and beetroot juice have ergogenic effects on endurance cycling performance. We investigated whether there is an additive effect of these supplements on the performance of a cycling time trial (TT) simulating the 2012 London Olympic Games course. Twelve male and 12 female competitive cyclists each completed 4 experimental trials in a double-blind Latin square design. Trials were undertaken with a caffeinated gum (CAFF) (3 mg·kg(-1) body mass (BM), 40 min prior to the TT), concentrated beetroot jui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 46 publications
3
81
1
2
Order By: Relevance
“…This may be explained by the elevated baseline plasma [NO 3 − ] and [NO 2 − ] in this cohort (Vassalle et al 2003), although multiple other factors may also be important (Jones 2014). It is therefore unclear whether the reduced effects of NO 3 − supplementation reported during longer vs. shorter duration exercise tests are related to the exercise duration (and requisite work rate) or the high training status of subjects in these investigations (Bescós et al 2012;Wilkerson et al 2012;Cermak et al 2012b;Lane et al 2014;Glaister et al 2015). Direct comparison between the effects of NO 3 − supplementation on short and longer duration (< or >30 min) exercise performance where other methodological variables are fixed is necessary, yet presently scarce.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This may be explained by the elevated baseline plasma [NO 3 − ] and [NO 2 − ] in this cohort (Vassalle et al 2003), although multiple other factors may also be important (Jones 2014). It is therefore unclear whether the reduced effects of NO 3 − supplementation reported during longer vs. shorter duration exercise tests are related to the exercise duration (and requisite work rate) or the high training status of subjects in these investigations (Bescós et al 2012;Wilkerson et al 2012;Cermak et al 2012b;Lane et al 2014;Glaister et al 2015). Direct comparison between the effects of NO 3 − supplementation on short and longer duration (< or >30 min) exercise performance where other methodological variables are fixed is necessary, yet presently scarce.…”
Section: Introductionmentioning
confidence: 88%
“…Notably, Lansley et al (2011) reported a significant and comparable improvement in 4 km (TT duration: ~6 min; performance improvement: 2.8%) and 16.1 km (TT duration: ~ 28 min; performance improvement: 2.7%) cycle ergometry TT performance in moderately trained males (VO 2max ~56 ml kg −1 min −1 ) consequent to NO 3 − ingestion. Conversely, NO 3 − supplementation has been reported to have a minimal effect on performance during longer duration (>30 min) exercise tests, which mandate a lower work rate (Bescós et al 2012;Wilkerson et al 2012;Cermak et al 2012b;Lane et al 2014;Glaister et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, well-trained participants (V O2max > 60 ml·kg -1 ·min -1 ) are typically less responsive to dietary nitrate supplementation [17,[19][20][21][25][26][27], even when very high nitrate doses (~ 19.5 mmol) are administered [28]. Highly-trained individuals are known to possess elevated baseline nitrate/ nitrite reserves [29], may habitually consume large amounts of nitrate, subsequent to their increased calorie consumption [30], and exhibit greater presence and activity of the NOS enzymes, relative to the untrained [31].…”
Section: Introductionmentioning
confidence: 99%
“…Gilchrist et al assessed neither plasma nitrite nor NO, this is necessary because NO response to inorganic nitrate supplementation varies widely between health and unhealthy elderly Lundberg JO et al 47 A recent meta-analysis Larsen FJ et al 48 evaluated data of beetroot juice supplementation effect on 24-hr ABPM (ambulatory blood pressure monitoring) in older subjects, it was concluded that nitrite concentrations, followed by inorganic nitrate ingestion, works as a potential factor influencing the association between inorganic nitrate and vascular responses. So, oral micro biota, gastric redo environment, oxygen tension and pH in the peripheral circulation or reeducates enzymes efficiency (factors that influence the conversion of inorganic nitrate to nitrite)need to be investigated in the elderly using inorganic nitrate supplementation to control BP levels Kenjale AA et al 49 In a study with mousse and rats Lane et al 50 it was verified that caffeine consumption inhibits NO synthesis (blocking NO syntheses) inducing cerebral artery constriction. Despite these opposite actions NO production from inorganic nitrate supplementation is an independent pathway of NO syntheses, 47 i.e., acts as a "backup" (preventing NO decrease) if a deficiency in the NO production occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with mousse and rats Lane et al 50 it was verified that caffeine consumption inhibits NO synthesis (blocking NO syntheses) inducing cerebral artery constriction. Despite these opposite actions NO production from inorganic nitrate supplementation is an independent pathway of NO syntheses, 47 i.e., acts as a "backup" (preventing NO decrease) if a deficiency in the NO production occurs.…”
mentioning
confidence: 97%